Pulmonary oedema caused by "liquid ecstasy" ingestion. Issue 4 (1st April 2002) - Piastra, M; Barbaro, R; Chiaretti, A; Tempera, A; Pulitanò, S; Polidori, G
Abstract : In this case report we describe the first recorded case of alveolar gas exchange impairment caused by "liquid ecstasy" ingestion, and perhaps inhalation, by a 4 year old child. The pulmonary gas diffusion disturbance was sufficiently prolonged to raise the suspicion of a direct toxic effect on the alveolar–capillary membrane.